THE PORTRAITS OF INDONESIAN WOMEN IN ADVERTISEMENTS - Puspitasari, Dewi; Hardini, Isriani (IAIN Pekalongan, 2012)
Abstract : The rise of advertisings that manipulate the role of women in which women are not positioned properly has proven that television or any other advertising media have exploited women. Studies have shown that the image of women that has predominated in advertisements is of weak, childish, dependent, domestic, irrational, subordinate creatures, the producers of children and little else compared with men. Often, women are positioned as objects possessing some system of signs: the lips, eyes, cheeks, hair, thighs, calves, hips, breasts, etc, those things become the fragments of mark in the patriarchy media, which is used to convey a particular meaning. Women are still oppressed and exploited again by culture - a culture of patriarchal. Various issues affecting women today is believed due to the hegemony of this culture that dominates all facets of life. Abstrak : Maraknya iklan-iklan yang memanipulasi peran perempuan di mana perempuan tidak benar diposisikan telah membuktikan bahwa televisi atau media iklan lainnya telah mengeksploitasi perempuan. Penelitian telah menunjukkan bahwa citra perempuan yang didominasi dalam iklan adalah lemah, kekanak-kanakan, tidak mandiri, domestik, irasional, makhluk bawahan, produsen anak-anak dan sedikit lain dibandingkan dengan laki-laki. Seringkali, perempuan diposisikan sebagai obyek memiliki beberapa sistem tanda: bibir, mata, pipi, rambut, paha, betis, pinggul, payudara, dan lain sebagainya. Halhal tersebut menjadi fragmen tanda di media patriarki, yang digunakan untuk menyampaikan makna tertentu. Perempuan masih tertindas dan dieksploitasi lagi oleh budaya-budaya patriarki. Berbagai persoalan yang dialami perempuan saat ini diyakini karena hegemoni budaya ini yang mendominasi semua aspek kehidupan.